Potential use of melastoma malabathricum as raw material for particleboard / Nurul Atiqah Hasbolah - Hasbolah, Nurul Atiqah (Faculty of Applied Sciences, 2017)
Melastoma malabathricum is a lesser known species that has the potential to make raw materials for producing particleboard. This species is easy to find in logged-over-forest forest and is easy to replant. The main objective of this study is to identify the mechanical and physical characteristics of the particleboard produced by Melastoma malabathricum species and to determine the effect of glue content on the size of the particles used. Modulus of Rupture (MOR). Modulus of Elasticity (MOE). Internal Bond (IB), Thickness Swelling (TS) and Water Absorption (WA) have shown that Melastoma malabathricum species have the potential to be used as raw materials in the wood industry